ANALYSIS OF VALUE ADDED OF PALM SUGAR IN SILAU RAKYAT VILLAGE, SEI RAMPAH SUBDISTRICT, SERDANG BEDAGAI REGENCY (CASE STUDY OF BU YUYUN AND BU RITA AGROINDUSTRIES) - Aprilia Putri; Adhiana; Wahyu Isnanda Nasution (Jurnal Mahasiswa Agribisnis, 2026)
This study aims to analyze and compare the value added generated from processing oil palm sap into palm sugar in Silau Rakyat Village, Sei Rampah Sub-district, Serdang Bedagai Regency. The study is motivated by the potential utilization of oil palm sap as an alternative raw material for palm sugar and the need to increase the value added of plantation commodities through agroindustrial activities. A case study approach was applied to two household-scale agroindustries with different production scales, namely Ms. Yuyun’s agroindustry with a larger production volume and Ms. Ritawati’s agroindustry with a smaller production volume. The analysis employed a quantitative approach using the Hayami value-added analysis method to calculate value added, value added ratios, and profits based on input–output relationships, labor use, and other supporting inputs in the production process. The results show that Ms. Yuyun’s agroindustry generates a value added of IDR 6,598.63 per kilogram with a value added ratio of 53.17% and a profit of IDR 5,758.63 per kilogram, while Ms. Ritawati’s agroindustry generates a value added of IDR 4,838.56 per kilogram with a value added ratio of 47.43% and a profit of IDR 4,138.56 per kilogram. Although both agroindustries are classified as having high value added ratios because they exceed 40%, the agroindustry with a larger production scale generates higher value added and profits. These findings indicate that production scale and efficiency in input utilization play an important role in increasing the economic value of oil palm sap palm sugar, highlighting its potential for development as a rural-based agroindustry. Keywords: Added Value, Brown Sugar, Oil Palm Sap